Microbiology of Diabetic Foot Infections in a Tertiary Care Hospital in São Paulo, Brazil - Amanda Thurler Palomo; Ana Paula Maia Pires; Marcelo Fernando Matielo; Rafael de Athayde Soares; Christiano Pecego; Roberto Sacilotto; Alexandre Inacio de Paula; Nair Hosino; Cristiano de Melo Gamba; Cibele Lefreve Fonseca; Daniela K. S. Paraskevopoulos; Augusto Yamaguti; et al. (MDPI AG, 2022)
Diabetic foot infections (DFIs) are one of the causes of hospitalization in diabetic patients and, when this occurs, empirical antibiotic therapy is necessary. We have conducted a retrospective study of patients with DFI that required hospitalization to evaluate microbiologic profile and the susceptibility pattern of these infections. We evaluated 320 patients, of which 223 (69.7%) were male with a media age of 71 years with 276 isolates. Gram-positive bacteria were responsible for 188 (68.1%) of the isolates, while Gram-negative bacilli were responsible for 88 (31.9%). E. faecalis was the most prevalent pathogen, followed by S. aureus and coagulase negative Staphylococci. Among Gram-negative pathogens, P. aeruginosa was the most prevalent agent. Regarding the susceptibility profile, we found ampicillin-sensitive enterococci in 89% of the cases, oxacillin-sensitive S. aureus in 47%, but in coagulase-negative staphylococci, oxacillin was sensible only in 20%. The susceptibility profile of Gram-negatives was very good with 76% susceptibility of P. aeruginosa to ceftazidime and meropenem. The other prevalent Enterobacterales had great susceptibility to ceftazidime, piperacillin-tazobactam and 100% susceptibility to meropenem, with the exception of K. pneumoniae, which had 75% susceptibility to meropenem. Knowledge of microbiological profile and susceptibility patterns of patients with DFIs is useful to guide empirical therapy.